The Stipulation of Settlement a debt of Commercial Transaction by a Documentary Credit - الشماع, فائق محمود (Journal of Legal Sciences, 2021)
Usually, International Trade Used to insert a condition for the settlement of Business transaction Debt through L/C method, by including a provision in the basic business transaction contract. Although this stipulation is prevalence but it does not have national legislative regulation outside USA, also it does not have unified assets and norms for L/Cs.Practical application refers to several conflict occurred regarding execution of the condition mentioned above, especially indicating commitment date for the Importer to open L/C on one hand, and the penalty resulting from breaching obligation by Importer on the other hand.In this research, detailed study will be presented about these two axes under the judgments of Iraqi law and comparative law.